Effects of cutting disturbance in Schoenoplectus californicus (C.A. Mey.) Soják on the benthic macroinvertebrates - doi: 10.4025/actascibiolsci.v33i1.6383 (Acta Scientiarum. Biological Sciences, 2011)
Lagoons are considered protected areas because these systems play a key ecological role. However, the extraction of macrophyte Schoenoplectus californicus is held for manufacture of handcrafts, being an alternative income for riverbank communities. This study evaluated the impact of S. californicus experimental cutting on benthic macroinvertebrates trough a field experiment. Macroinvertebrates were sampled at 1, 12, 26 and 60 days after the macrophyte cutting in demarked plots (1 m²), as well at control plots. The families number was not statistically different (ANOVA, p > 0.05), but the total density of invertebrates, and the density of Ceratopogonidae were significant (ANOVA, p < 0.05) for interaction between sampling date and treatment. A Principal Components Analysis identified that the level of the water column was the variable that most influenced the variation between the samples gathered in the experiment. We concluded that the cutting of S. californicus, in this area, as the intensity of the cut held, did not affect considerably the aquatic macroinvertebrates. The results suggest that the small-scale extractivism in these regions carries little effect because the fauna of adjacent areas probably can quickly colonize the disturbed areas.